2023
DOI: 10.1126/sciadv.adh8152
|View full text |Cite
|
Sign up to set email alerts
|

A mechanochemical model recapitulates distinct vertebrate gastrulation modes

Mattia Serra,
Guillermo Serrano Nájera,
Manli Chuai
et al.

Abstract: During vertebrate gastrulation, an embryo transforms from a layer of epithelial cells into a multilayered gastrula. This process requires the coordinated movements of hundreds to tens of thousands of cells, depending on the organism. In the chick embryo, patterns of actomyosin cables spanning several cells drive coordinated tissue flows. Here, we derive a minimal theoretical framework that couples actomyosin activity to global tissue flows. Our model predicts the onset and development of gastrulation flows in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Accordingly, a mechanically motivated framework for studying development has provided increasingly cross-disciplinary insights, particularly over the past two decades. This physically-motivated view of development has revealed that mechanisms of morphogenesis can be understood using purely mechanical descriptions, providing insights even in the absence of implicating genes or signaling pathways per se (Mongera et al, 2018; Saadaoui et al, 2020; Savin et al, 2011; Serra et al, 2023; Shyer et al, 2013; Tallinen et al, 2014). At the same time, physical forces and mechanical properties have begun to be recognized as guiding cell behaviors and gene expression as well, revealing mechanics as an important upstream regulator of cell behaviors during development (Barriga et al, 2018; Farge, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a mechanically motivated framework for studying development has provided increasingly cross-disciplinary insights, particularly over the past two decades. This physically-motivated view of development has revealed that mechanisms of morphogenesis can be understood using purely mechanical descriptions, providing insights even in the absence of implicating genes or signaling pathways per se (Mongera et al, 2018; Saadaoui et al, 2020; Savin et al, 2011; Serra et al, 2023; Shyer et al, 2013; Tallinen et al, 2014). At the same time, physical forces and mechanical properties have begun to be recognized as guiding cell behaviors and gene expression as well, revealing mechanics as an important upstream regulator of cell behaviors during development (Barriga et al, 2018; Farge, 2003).…”
Section: Introductionmentioning
confidence: 99%